ANALISIS FAKTOR YANG BERPENGARUH TERHADAP PRODUKSI KARET DI PT PERKEBUNAN NUSANTARA IX KEBUN SUKAMANGLI KABUPATEN KENDAL - Eko Setyawan; Renan Subantoro; Rossi Prabowo (Universitas Wahid Hasyim, 2016)
Rubber plant productivity is affected by production factors such as amount of labour, amount of land area, number of productive tree, manure and rainfall. Production factors must be controlled to meet optimum rubber production, due to the increasing need of rubber. Rubber consumption on 2009 is 9,277 millions ton, while on 2010 increase become 10,664 millions ton. World crude rubber is able to provide 9,702 millions ton on 2009 and 10,219 million ton on 2010. Factor that influence rubber harvest result is the benchmark to get the decision to support the rubber achievement harvest optimally. The purposes of this research is to know the production factor that influence rubber production in PT Perkebunan Nusantara IX (PTPN IX) Sukamangli estate. This research used descriptive analytical method. The data analysis uses multiple linear regresion with dummy. The regression analysis showed regression equation do not contain symptoms multikolinier, autocorrelation, heterokedastisitas. While the production factor significantly rubber production are amount of the harvesting of labour, amount of land area, the number of tree/hectare, cost of production, Ethrel stimunlansia, dummy tapping system and dummy tapping technology. Based on regression analysis, production factors that partially significantly influencing the rubber production is the harvest of labour, amount of land area, the number tree/hectare, cost of production, Ethrel stimulansia, dummy tapping system and dummy tapping technology. Keywords: production factors, rubber production, multiple regression, ARIMA